Predicaments of entrepreneurship in transitional Russia. (1st January 2013) - Timofeyev, Yuriy; Yan, Ho-Don
The collapse of the Soviet Union's central-planned economy vindicates that resources' allocation under communist rule was woefully deficient and ultimately gave way to a market economy. For the successful transformation from communism, entrepreneurship is immediately needed. This study highlights three main activities in the entrepreneurial process, including opportunity discovery, mobilisation of resources, and organisation creation, which are the factors we focus on while discussing the predicaments of the entrepreneurial process. We also emphasise the importance of surrounding institutions in which entrepreneurial activities are embedded. Based on analysing the entrepreneurial process, we argue that given a systemic way to identify the underlying predicaments of the entrepreneurial process in transition economies, the issues confronting transition economies can be aptly grasped.